Clinical characteristics of small bowel tumors diagnosed by double-balloon endoscopy: Experience from a Chinese tertiary hospital - Chen Zhang; Liwen Hong; Tianyu Zhang; Peijun Sun; Juntao Sun; Jie Zhou; Lei Wang; Rong Fan; Zhengting Wang; Shidan Cheng; et al. (Turkish Journal of Gastroenterology, 2020)
Background/Aims: To determine the characteristics of small bowel tumors (SBTs) in patients underwent double balloon endoscopy (DBE) and to compare the clinical value of DBE with other diagnostic tools. Materials and Methods: A retrospective study was conducted in patients underwent DBE procedures from March 2008 to April 2017.The demographic, clinical and pathological characteristics of patients with SBTs were recorded, while the diagnosis of SBTs was achieved either by DBE biopsy or surgical specimens. Results: One thousand one hundred and two patients (761 males, range 3-85 years) were enrolled in this study, with 1140 procedures completed in total. 99/1102 patients (9.0%) had SBTs, including benign polyps (20, 20.2%), gastrointestinal stromal tumors (GISTs) (24, 24.2%), lymphomas (13, 13.1%), adenocarcinoma (39, 39.4%), and neuroendocrine tumors (3, 3.0%). The most common clinical symptom for benign polyps was obscure gastrointestinal bleeding (OGIB) (75.0%). But among patients with malignant SBTs, the main indication for DBE was chronic abdominal pain (43.8%), followed by OGIB (36.3%), vomit (10.0%), abnormal images (6.3%) and diarrhea (3.8%) (P<0.001). Moreover, SBTs were primarily located in the jejunum alone (40/99, 40.4%). DBE had better sensitivity (89.2%), specificity (95.2%), positive predictive value (PPV) (90.0%), and negative predictive value (NPV) (94.8%) than other tools for suspected SBTs. Conclusion: Small bowel tumor is mainly located in jejunum and with OGIB and abdominal pain as major complaints. DBE is a reliable method for the diagnosis of SBTs compared with other diagnostic tools. Cite this article as: Zhang C, Hong L, Zhang T, et al. Clinical characteristics of small bowel tumors diagnosed by double-balloon endoscopy: Experience from a Chinese tertiary hospital. Turk J Gastroenterol 2020; 31(1): 30-5.